The structure of collective contracting in China. (1st October 2016) - Liu, Ziheng; Sun, Shaobo; Bray, Mark
ABSTRACT: The use of 'collective contracts', established through the process of 'collective consultation', to set the wages and working conditions of employees in China has increased dramatically over recent years. This paper offers an analysis of this important trend that is distinctive in three ways. First, we reflect on the meaning of collective contracting and collective consultation and distinguish them more conventional Western concepts of collective agreements and bargaining. Second, we suggest a framework – drawn from the well-established literature on the structure of collective bargaining – for analysing collective contracting in China. Third, by applying this framework to the existing empirical evidence – derived from publicly available data and published scholarly research – we provide an account of collective contracting in China that is more comprehensive than the existing literature and which clearly identifies the role of the state as central.